The labor market of digital labor platforms in Chile: companies, state regulation and workers - Stecher, Antonio; Morales, Karol; Valenzuela, Alan (Frontiers in Sociology, 2025)
IntroductionIn Chile, as in different Latin American countries, a growing expansion of digital labor platforms has been observed since 2010. The study of the labor markets of these platforms in countries such as Chile is of great importance to understand the particularities that these companies acquire in contexts other than the global north. Contexts with high rates of informal employment and fragile labor institutions give rise to particular dynamics and configurations in these labor markets. In turn, the case of Chile is of special interest due to the recent approval of a law (21.431)—the first of its kind in Latin America- regulating the contract of delivery and transportation platform workers, as well as its pioneering role in the processes of neoliberal modernization in the region, which are at the basis of many of the current productive and labor dynamics of the platforms.MethodsThe reconstruction of the delivery and ride-hailing digital platforms labor market is based on the analysis of data (interviews with workers, interviews with key informants, documentary analysis of primary sources, review of secondary sources, field observations) collected between 2019 and 2025 in the framework of three research projects.Results and discussionWe present a reconstruction of the delivery and ride-hailing digital platforms labor market organized around three axes: (i) platform companies, (ii) state labor regulations, and (iii) workers. The analysis incorporates a diachronic perspective that highlights key milestones in the development of this labor market in Chile between 2010 and 2025, accounting for its dynamism and transformation. Likewise, a perspective is incorporated that accounts for the role of different actors—business actors, State actors (legislative, executive, and judicial branches) and worker organizations- in shaping the labor market of digital work platforms in Chile. The article concludes by identifying three key characteristics of this labor market: (i) its heterogeneity, (ii) an internal logic that amplifies and naturalizes precariousness, and (iii) its capacity to offer possibilities for rapid job insertion and precarious social inclusion.